2022
DOI: 10.1096/fj.202200637r
|View full text |Cite
|
Sign up to set email alerts
|

Maternal L‐carnitine supplementation promotes brown adipose tissue thermogenesis of newborn goats after cold exposure

Abstract: Brown adipose tissue (BAT) is an important component of energy expenditure and necessary to maintain body temperature for newborn mammals. In the previous study, we found that L‐carnitine was enriched in BAT and promoted BAT adipogenesis and thermogenesis in goat brown adipocytes. However, whether dietary L‐carnitine regulates BAT heat production and energy expenditure in lambs remains unclear. In this study, maternal L‐carnitine supplementation elevated the rectal temperature, as well as the expression of UCP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 63 publications
(115 reference statements)
0
4
0
Order By: Relevance
“…l -carnitine promotes the β oxidation of long-chain fatty acids across mitochondrial membranes, which in turn promotes energy metabolism 70 . Dietary supplementation with l -carnitine has been shown to increase the growth rate of weaned calves and feed conversion in lambs 71 , 72 , and maternal l -carnitine supplementation has been shown to promote the development and thermogenesis of white adipose tissue in neonatal goats 73 . l -carnitine supplementation has been shown to increase plasma IGF-1 levels 74 , 75 and play an important role in muscle cell proliferation 76 and increase birth weight 77 .…”
Section: Discussionmentioning
confidence: 99%
“…l -carnitine promotes the β oxidation of long-chain fatty acids across mitochondrial membranes, which in turn promotes energy metabolism 70 . Dietary supplementation with l -carnitine has been shown to increase the growth rate of weaned calves and feed conversion in lambs 71 , 72 , and maternal l -carnitine supplementation has been shown to promote the development and thermogenesis of white adipose tissue in neonatal goats 73 . l -carnitine supplementation has been shown to increase plasma IGF-1 levels 74 , 75 and play an important role in muscle cell proliferation 76 and increase birth weight 77 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, maternal L-carnitine supplementation increased the rectal temperature of newborn goats and promoted BAT thermogenesis. Further research found that L-carnitine promoted TG and glycogen deposition in brown adipocytes through AMPKα [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, these effects were found to be recoverable with l -carnitine supplementation [ 80 ]. Another finding observed in newborn goats indicates that maternal l -carnitine supplementation enhances BAT development and thermogenesis [ 81 ]. This underscores the significance of maternal nutrition in the development of mammalian infants.…”
Section: Nutritional Factors Regulate Bat Activitymentioning
confidence: 99%